Analisis Fungsi Bahasa yang Digunakan oleh Presiden Prabowo dalam Pidato di PBB Pada Tahun 2025 - Husnul Hotimah; Condro Nur Alim (BASIS (Bahasa dan Sastra Inggris), 2026)
This study uses the theoretical framework proposed by Roman Jakobson to examine how language is used in President Prabowo’s speech at the United Nations in 2025. The purpose of this study is to explain the various types of language functions used by President Prabowo in his speech at the UN, how these language functions are realized, and how the use of language functions can reinforce political messages. Descriptive qualitative research was applied to examine the transcript of President Prabowo’s state address. The sources of information for this study were words, clauses, and sentences taken from the text of the speech on the official website of the Secretariat of the Republic of Indonesia. The results of this study show that the speech contains all of Roman Jakobson’s language functions: referential, emotive, conative, phatic, metalingual, and poetic. The use of these language functions helps to construct a straightforward and easily understood political message, which can strengthen Indonesia’s diplomatic position on the world stage.